Interim Prosthetic Rehabilitation of a Patient Following Partial Rhinectomy: A Clinical Report - Guttal, Satyabodh S.; Vohra, Paras; Pillai, Lekha K.; Nadiger, Ramesh K. (European Journal of Dentistry, 2010)
Surgical defects often have adverse effects on patient perception of esthetics and self-esteem. Rehabilitation of such surgical defects poses a challenge to the clinician. Presented here is a clinical report of an interim prosthetic rehabilitation of a patient who underwent partial rhinectomy for basal cell carcinoma. Nasal resection included part of the nasal septum, the entire cartilage, and the ala. An interim nasal prosthesis was fabricated for this patient 3 weeks after surgery, to provide early rehabilitation. This prosthesis provided a sociopsychological benefit to the patient, and the prosthesis was well tolerated. The spectacle glasses retained the prosthetic nose. (Eur J Dent 2010;4:482-486)
Keywords: Nasal prosthesis; Maxillofacial prosthesis; Immediate prosthetic replacement